Efficiency of mineral fertilization of spring wheat - Timofeev Vyacheslav; Vyushina Olga (BIO Web of Conferences)
The results of application of Agree’s leaf mineral fertilizer on spring wheat in the system of complex crop protection under conditions of insufficient moisture are presented. Field studies were carried out in the northern forest-steppe zone of the Tyumen region in the experimental fields of the Scientific Research Institute of Agriculture for Northern Trans-Ural Region - Branch of Federal State Institutions Federal Re-search Centre Tyumen Scientific Centre of Siberian Branch of the Russian Academy of Sciences. According to the results of the research, the positive effect of Agree’s NK liquid complex fertilizer in the complex of plant protection products application on the parameters of plant structural elements was revealed. Increase in ear length by 1.4 cm, number of spikelets by 2.5 pieces, number of grains in the ear by 6 pcs, weight of grain from 25 stems by 6-16 g, weight of 1000 grains by 4 g according to variants of agrochemicals application in tillering and earing phases: No 3 Agree’s NK, 2 l/ha + Agree’s NK, 2 l/ha; No 6 Agree’s N, 2 l/ha + Agree’s NK, 2 l/ha; No 7 Agree’s N, 3 l/ha + Agree’s NK, 2 l/ha. Application of agrochemicals in one phase of crop development, maximum rates had no positive effect on spring wheat yield. Application of agrochemical schemes Agree’s NK, 2 l/ha + Agree’s NK, 2 l/ha; Agree’s N, 2 l/ha + Agree’s NK, 2 l/ha; Agree’s N, 3 l/ha + Agree’s NK, 2 l/ha increased yield to 0.6-0.8 t/ha or 24-31%. The application of agrochemical Agree’s in the phase of the beginning of earing contributed to the improvement of technological quality of wheat grain, gluten content was higher than the control by 2-4%. Gluten quality 75-100 units, which is satisfactory. The use of agrochemicals has a clear advantage in the treatment of plants on the leaf in the system of their protection, an integrated approach to the use of agrochemicals is necessary, taking into account the treatment of at least 2 phases of plant development or one, but in the phase of unfolding of the flag leaf and the beginning of earing.